Reporte de las familias sobre los patrones de actividad física extraescolar en niñas y niños de educación infantil (2016)
Early childhood education is an important opportunity in order to promote healthy habits. In doing so, it has been shown that parents attitudes, values and knowledge in relationship with physical activity could be determine children´s behaviours. For this reason, the main aim of this descriptive-exploratory study is to determine the parents perception of physical activity patterns of children between 3-4 years old from a public school of Valencia, Spain. It was used a previously validated questionnaire. Only 50% of the families reported that children participated in leisure time activities outside school. Of them, 50% and 38% participated during 2 and 1 time, respectively. 60% and 22% reported that children visited the parks 2 and 1 time per weeks, respectively. 70% used active commuting transport to the school. 42% of the families perceived that their children do activities in static position. Despite the fact that families considered that their children are more active than their counterparts, only 20% considered that the best phrase in order to describe their children suggested that they do not stop to move. In conclusion, it is recommended a collaborative work between teachers, families and schools in order to find alternatives to reduce the high levels of sedentary behaviors, overweight, obesity and children under 6 years old.